Falling Short : A Global Survey of Electricity Tariff Design - Foster, Vivien; Witte, Samantha (World Bank, Washington, DC, 2020)
This paper provides a comprehensive overview of electricity pricing practices and tariff structure design in more than 60 developed and developing countries worldwide as of 2015-16. It evaluates the performance of electricity tariff designs according to a variety of important dimensions, notably cost recovery, vertical equity (affordability), and horizontal equity (or price differentiation). It also reflects on the extent to which current electricity tariff designs are well-suited to incentivize efficient adoption of emerging technologies, such as distributed generation and storage, electric vehicles, and demand-side participation. The results of the survey indicate that electricity tariffs stand at $0.13 per kilowatt-hour (when fully averaged across countries and customer groupings); but differ hugely across jurisdictions by a factor of 40:1. Electricity tariffs are far from recovering limited capital costs and have not kept up with inflation over time. Substantial price differentiation is the norm, and affordability remains a significant concern. Most countries' tariff structures are ill-adapted to emerging technological disruption in the sector, due to the scant use of load-related charges to cover the fixed costs of the network, the continued preponderance of increasing block tariffs for residential customers, and the limited application of time-of-use pricing.